DEVELOPMENT OF SOFTWARE FOR SHEEP MANAGEMENT - Fernandes, Lucas Mangelo; China, Anna Patricia Zakem (Revista Interface Tecnológica, 2020)
This article aims to present a software development that intends to serve all the needs of sheep producers, it contemplates the main phases that are of great importance for monitoring and raising the animal. It presents the processes of sheep care, the technological choices made to create a product that focuses on the user experience, with an easy to use graphic interface and accessible to rural producers. The solution presented seeks to be a tool to identify the evolution of the herd, thus making it possible to reduce costs and increase productivity, as well as apply traceability of the animal in all its life circle.